Does credit composition have asymmetric effects on income inequality? New evidence from panel data - Ünal Seven; Dilara Kilinc; Yener Coskun (International Journal of Financial Studies, 2018)
This paper studied the effects of credit to private non-financial sectors on income inequality. In particular, we focused on the distinction between household and firm credits, and investigated whether these two types of credit had adverse effects on income inequality. Employing cross-section augmented cointegrating regressions and using balanced panel data for 30 developed and developing countries over the period from 1995 to 2013, we showed that firm credit reduced income inequality, whereas there was no significant impact of household credit on income inequality. We concluded that it was not the size of the private credit but its composition which mattered in reducing income inequality, due to the asymmetric effects of different types of credit.
Keywords: G20; D31; O16; D60; 330; household credit; firm credit; income inequality; credit composition; mean group estimator